Stimulation of TLR4 by LMW-HA Induces Metastasis in Human Papillary Thyroid Carcinoma through CXCR7 - Shipeng Dang; Yongde Peng; Lei Ye; Yanan Wang; Zhongqing Qian; Yuqing Chen; Xiaojing Wang; Yunzhi Lin; Xiaomei Zhang; Xiyan Sun; Qiong Wu; Yiji Cheng; et al. (Clinical and Developmental Immunology)
In inflammatory sites, high molecular weight hyaluronan fragments are degraded into lower molecular weight hyaluronan fragments (LMW-HA) to regulate immune responses. However, the function of LMW-HA in PTC progression remains to be elucidated. In this study, we found that receptor of LMW-HA, TLR4, was aberrantly overexpressed in PTC tissues and cell line W3. Exposure of W3 cells to LMW-HA promoted cell proliferation and migration via TLR4. Knockdown of TLR4 has provided evidence that TLR4 is essential for LMW-HA-induced CXCR7 expression, which is responsible for LMW-HA-induced proliferation and migration of W3 cells. In tumor-bearing adult nude mice, stimulation of LMW-HA on W3 cells promotes CXCR7 expression in tumor masses (P=0.002) and tumor growth (P<0.001). To further confirm our findings, we investigated the clinicopathologic significance of TLR4 and CXCR7 expression using immumohistochemistry in 135 human PTC tissues and 56 normal thyroid tissue samples. Higher rates of TLR4 (53%) and CXCR7 (24%) expression were found in PTC tissues than in normal tissues. Expression of TLR4 or CXCR7 is associated with tumor size and lymph node metastasis. Therefore, LMW-HA may contribute to the development of PTC via TLR4/CXCR7 pathway, which may be a novel target for PTC immunomodulatory therapy.